2017
DOI: 10.1001/jamaoto.2016.4749
|View full text |Cite
|
Sign up to set email alerts
|

Experience of US Patients Who Self-identify as Having an Overdiagnosed Thyroid Cancer

Abstract: Isolation and anxiety characterize the current experience of patients with thyroid cancer who are living with the decision to not intervene. These patients are at risk of disengaging from health care. Successful de-escalation of intervention for patients who self-identify as having overdiagnosed cancers requires explicit social and health system support and education. We hypothesize that improved support would also promote quality of care by increasing the likelihood that patients could be kept engaged for rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…Patients with recognized overdiagnosed thyroid cancer who opted against aggressive care have reported anxiety and feelings of isolation and secret keeping,67 though evidence in other clinical settings is limited. However, the psychological ramifications of disease diagnoses probably apply to overdiagnosis as well as to legitimate diagnoses 68.…”
Section: Consequences Of Overdiagnosismentioning
confidence: 99%
“…Patients with recognized overdiagnosed thyroid cancer who opted against aggressive care have reported anxiety and feelings of isolation and secret keeping,67 though evidence in other clinical settings is limited. However, the psychological ramifications of disease diagnoses probably apply to overdiagnosis as well as to legitimate diagnoses 68.…”
Section: Consequences Of Overdiagnosismentioning
confidence: 99%
“…Keeping with this, our group recently showed that the incidence of thyroid cancer is higher in states with higher rates of malpractice payout. 6 The association held when controlling for other thyroid cancer risk factors, including health care access. The study concludes malpractice climate may be a social determinant of thyroid cancer risk.…”
Section: Thyroid Cancer Overdiagnosis and Malpractice Climatementioning
confidence: 97%
“…It also may help to prevent ostracism and isolation of patients who request noninterventional follow-up. Sadly, Davis et al 6 recently found that some patients who believed themselves overdiagnosed and requested nonintervention for atypical, suspicious, or ''malignant'' thyroid nodules felt that they were denied the support of their physicians and friends. One was even called ''stupid.''…”
Section: Thyroid Cancer Overdiagnosis and Malpractice Climatementioning
confidence: 99%
“…If a UIP pattern is recognized, it is important to specify if patchy fibrosis, fibroblast foci, and honeycomb changes are present or absent, as well as the corresponding level of confidence (high or low, according to the recently updated criteria). 6,7 On the other hand, if UIP pattern is recognized, it should be specified if ancillary findings suggesting chronic hypersensitivity pneumonitis or collagen vascular dis-ease or asbestosis (eg, chronic lymphoplasmacytic inflammation with or without lymphoid follicles, interstitial granulomas/giant cells, bronchiolitis, pleuritis, bridging fibrosis, asbestos fibers, eosinophilic infiltrate) are present or absent/minimal. A specific diagnosis should be reported (eg, Langerhans cell histiocytosis, lymphangioleiomyomatosis, pulmonary alveolar proteinosis); if no specific pattern is identified (either normal lung or unclassifiable fibrosis), a descriptive diagnosis could be made.…”
Section: Diagnostic Report For Everymentioning
confidence: 99%